PENERAPAN ARSITEKTUR HIJAU PADA PERANCANGAN TERMINAL PENUMPANG DAN WISATA AIR PELABUHAN KOHOD DI KABUPATEN TANGERANG - Gian Angraini Fisamawati; Putri Suryandari (MAESTRO, 2019)
The Application of Green Architecture in the Design of the Kohod Port Passenger and Water Tourism Terminal in Tangerang Regency can be interpreted as a place or building that serves to accommodate and serve the anchored needs of ships for public passengers and water tourism activities by implementing energy saving and natural resource use concepts efficiently and optimal, and provide water tourism facilities as an attraction. The Tangerang Passenger Terminal and Water Tourism Port of Tangerang Regency have been synthesized in the form of a design concept. This development plan seeks to provide a function of the building of sea transportation facilities as a branch port of Tanjung Priok which is specifically for passengers. This port is designed with a green architecture approach that utilizes the conditions of local natural resources. This Architectural Concept seeks to implement energy-saving and environmentally friendly ways to provide comfort for users and the environment.